SKRINNING FITOKIMIA, UJI AKTIVITAS ANTIOKSIDAN DAN TABIR SURYA PADA TANAMAN JAGUNG (Zea mays L.) - Pangemanan, David Albert; Suryanto, Edi; Yamlean, Paulina V. Y. (UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACT Corn (Zea Mays L.) is widely developed in Indonesia. Corn kernels showed total phenolic and antioxidant activity. Antioxidants have the potential as photoprotectors, therefore, plants containing phenolic compounds can be used in the prevention of free radicals. For this reason, researcher is interested in further researching the phytochemical screening, antioxidant activity and sunscreen testing from extracts of stems, leaves, hair and leaf wrapping from corn (Zea mays L.). The samples used were corn plants (corn silk, corn leaves, corn stalks and leaf wrapping corn) originating from Kauditan area, North Minahasa. The results of the study showed that the leaf contained saponin and flavonoid compounds, the stem contained alkaloid and saponin compounds, the hair contained alkaloid and flavonoid compounds, and the leaf wrapping only contained alkaloid compounds. The highest to lowest total phenolic content values starting from the stem were 46.93 μg / mL, the leaf wrapping 37.76 μg / mL, the leaf 26.63 μg / mL and hair 14.49 μg / mL. The leaf has the highest antioxidant activity with a value of 72.81% followed by 62.87% stem then wrapping leaf 43.13% and finally hair 29.14%. The SPF value of the stem was included in the ultra protection with a value of 16.117 followed by the leaves included in the maximum protection with an SPF value of 10.902. While the hair with SPF value of 0.6 and wrapping leaf with SPF value of 0.222 are included in the minimum protection. Keywords: Corn (Zea Mays L.), Sunscreen, Antioxidants, Phenol ABSTRAK Jagung (Zea Mays L.) banyak dikembangkan di Indonesia. Biji jagung menunjukkan kadar total fenolik dan aktivitas antioksidan. Antioksidan memiliki potensi sebagai fotoprotektor, oleh karena itu, tanaman yang mengandung senyawa fenolik dapat digunakan dalam pencegahan radikal bebas. Untuk itu peneliti tertarik untuk meneliti lebih lanjut tentang skrining fitokimia, uji aktivitas antioksidan dan tabir surya dari ekstrak batang, daun, rambut, dan daun pembungkus dari jagung (Zea mays L.). Sampel yang digunakan ialah tanaman jagung (rambut jagung, daun jagung, batang jagung dan daun pembungkus jagung) yang berasal dari daerah Kauditan, Minahasa Utara. Hasil dari penelitian menunjukkan daun mengandung senyawa saponin dan flavonoid, batang mengandung senyawa alkaloid dan saponin, rambut mengandung senyawa alkaloid dan flavonoid, dan daun pembungkus hanya mengandung senyawa alkaloid. Nilai kandungan total fenolik yang paling tinggi sampai paling rendah dimulai dari batang sebesar 46.93 μg/mL, daun pembungkus 37.76 μg/mL, daun 26.63 μg/mL dan rambut 14.49 μg/mL. Daun memiliki aktivitas antioksidan yang paling tinggi dengan nilai 72.81% diikuti oleh batang 62.87% kemudian daun pembungkus 43.13% dan yang terakhir adalah rambut 29.14%. Nilai SPF batang termasuk dalam proteksi ultra dengan nilai 16,117 diikuti oleh daun yang termasuk dalam proteksi maksimal dengan nilai SPF 10,902. Sedangkan rambut dengan nilai SPF 0,6 dan daun pembungkus dengan nilai SPF 0,222 termasuk dalam proteksi minimal. Kata Kunci : Jagung (Zea Mays L.), Tabir Surya, Antioksidan, Fenol